Emerging dimensions in Fintech: Insights from bibliometric analysis - Mahak Sethi; Narendra Singh Bohra; Amar Johri; Mohammad Asif (Digital Business, 2025)
Fintech has emerged as a transformative force in the financial industry, promoting inclusivity and efficiency. This study aims to conduct a comprehensive bibliometric analysis of 1416 articles sourced from the Scopus database to map the evolution of fintech research. Employing the PRISMA methodology and VOS viewer software, we identify influential authors, key citations, and leading journals in this domain. Our findings indicate a significant increase in fintech research output since 2015, with China and the UK being the foremost contributors. Notably, the UK leads with the highest average citations per article, underscoring its research quality. Prominent journals identified include Sustainability (Switzerland) and IEEE Access. Despite this growth, our analysis reveals critical gaps in literature regarding financial inclusion, digital finance, and sustainability, which are vital for serving underbanked populations and advancing green finance initiatives. Furthermore, research on emerging technologies such as AI, blockchain, and robo-advisors remains limited, presenting substantial opportunities for future exploration. This study highlights the globalization of fintech research through contributions from diverse countries and outlines key trends shaping the field. It not only assesses the current landscape but also raises pertinent research questions to guide future investigations. While limited to articles from Scopus, this analysis serves as a crucial roadmap for future research directions.
Keywords: 650; Bibliometric analysis; Digital finance; Financial inclusion; Fintech